2021
DOI: 10.1139/cjz-2020-0280
|View full text |Cite
|
Sign up to set email alerts
|

Determining the influence of snow and temperature on the movement rates of wood bison (Bison bison athabascae)

Abstract: Snow is understood to limit wildlife movements, often being the most important determinant of winter movement for animals in the boreal forest. However, the combined effect of snow and temperature on the movement ecology of animals at high latitudes is less understood. We used GPS-collar data from a small population of wood bison (Bison bison athabascae Rhoads, 1898) in northeastern Alberta, Canada to develop a series of generalized additive mixed models characterizing the effect of cumulative snow depth, dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Lastly, we collected five climatic variables and averaged their values within each 1-km pixel [39]. We considered annual precipitation as snow and mean temperature of the coldest month to be indicative of snow depth and winter severity, which have been previously shown to affect bison distribution [40,41]. The other three climatic variables were mean annual solar radiation, mean summer precipitation, and mean temperature of the warmest month, which we considered indicative of primary productivity and thus forage availability for bison.…”
Section: Bottom-up Effects On Bisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we collected five climatic variables and averaged their values within each 1-km pixel [39]. We considered annual precipitation as snow and mean temperature of the coldest month to be indicative of snow depth and winter severity, which have been previously shown to affect bison distribution [40,41]. The other three climatic variables were mean annual solar radiation, mean summer precipitation, and mean temperature of the warmest month, which we considered indicative of primary productivity and thus forage availability for bison.…”
Section: Bottom-up Effects On Bisonmentioning
confidence: 99%
“…Despite these bottom-up and top-down limits imposed on historical bison distribution, recent restoration projects have achieved rapid bison population growth in areas that were historically on the fringe or outside of what we identified as suitable habitat (Figure 3, Table 2). The success of these projects demonstrates that bison are clearly adapted to thrive in a broad range of climates, vegetation conditions, and predators, even if snow depth [40], forage quality and availability [105] and non-human predation [106] influence their localized spatial distribution. Recent studies have also demonstrated remarkable plasticity in bison diets across North America [107,108], providing further evidence that bison can thrive in a variety of conditions.…”
Section: Implications For Bison Restoration In the Western Cordilleramentioning
confidence: 99%
“…Lastly, we collected five climatic variables from a global climate model at a 1km pixel size, which were quantified from climate normal between 1961 and 1990 [47]. We considered annual precipitation as snow and mean temperature of the coldest month to be indicative of snow depth and winter severity, which have been previously shown to affect bison distribution [48,49]. The other three climatic variables were mean annual solar radiation, mean summer precipitation, and mean temperature of the warmest month, which we considered indicative of primary productivity and thus forage availability for bison.…”
Section: Bottom-up Effects On Bisonmentioning
confidence: 99%
“…Despite these bottom-up and top-down limitations imposed on historical bison distribution, recent restoration projects have achieved rapid bison population growth in areas that were historically on the fringe or outside of what we identified as suitable habitat (Figure 3, Table 2). The success of these projects demonstrates that bison can thrive in a broad range of climates, vegetation conditions, and predators, even if snow depth [48], forage quality and availability [116] and non-human predation [117] influence their localized spatial distribution. Recent studies have also demonstrated remarkable plasticity in bison diets across North America [118,119], and MaxEnt ecological niche modelling based on fossil records of bison and historic climates demonstrated that much of North America was suitable bison habitat over the past 20,000 years [13].…”
Section: Implications For Bison Restoration In the Western Cordilleramentioning
confidence: 99%
“…Many large ungulates are also predicted to experience climate change‐induced range boundary shifts (Thomas, 2010 ), which further complicates ongoing conservation efforts for those species already restricted to small areas due to human encroachment. While many studies have addressed how ungulate habitat selection changes in response to physical landscape features (e.g., phenology, topography, roads; Geremia et al, 2019 ; Merkle et al, 2016 ; O'Shaughnessy et al, 2014 ), relatively few have attempted to address how their movement—regardless of the underlying landscape—is affected by weather (Boyers et al, 2019 ; Schmidt et al, 2016 ; Sheppard et al, 2021 ). Understanding how ungulates respond to weather is critical for predicting the long‐term consequences of climate change and informing their conservation in the Anthropocene.…”
Section: Introductionmentioning
confidence: 99%